What will it take to achieve virtual elimination of mother-to-child transmission of HIV? An assessment of current progress and future needs. (23rd November 2010) - Mahy, Mary; Stover, John; Kiragu, Karusa; Hayashi, Chika; Akwara, Priscilla; Luo, Chewe; Stanecki, Karen; Ekpini, Rene; Shaffer, Nathan
Abstract : Background: The number of HIV-positive pregnant women receiving antiretroviral drugs (ARVs) to prevent mother-to-child transmission (MTCT) of HIV has increased rapidly. Objective: To estimate the reduction in new child HIV infections resulting from prevention of MTCT (PMTCT) over the past decade. To project the potential impact of implementing the new WHO PMTCT guidelines between 2010 and 2015 and consider the efforts required to virtually eliminate MTCT, defined as <5% transmission of HIV from mother to child, or 90% reduction of infections among young children by 2015. Methods: Data from 25 countries with the largest numbers of HIV-positive pregnant women were used to create five scenarios to evaluate different PMTCT interventions. A demographic model, Spectrum, was used to estimate new child HIV infections as a measure of the impact of interventions. Results: Between 2000 and 2009 there was a 24% reduction in the estimated annual number of new child infections in the 25 countries, of which about one-third occurred in 2009 alone. If these countries implement the new WHO PMTCT recommendations between 2010 and 2015, and provide more effective ARV prophylaxis or treatment to 90% of HIV-positive pregnant women, 1 million new child infections could be averted by 2015. Reducing HIV incidence in reproductive age women, eliminating the current unmet need for family planning and limiting the duration of breastfeeding to 12 months (with ARV prophylaxis) could avert an additional 264 000 infections, resulting in a total reduction of 79% of annual new child infections between 2009 and 2015, approaching but still missing the goal of virtual elimination of MTCT. Discussion: To achieve virtual elimination of new child infections PMTCT programmes must achieve high coverage of more effective ARV interventions and safer infant feeding practices. In addition, a comprehensive approach including meeting unmet family planning needs and reducing new HIV infections among reproductive age women will be required.